2021
DOI: 10.3389/fmars.2020.574455
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Connectivity of the West Indian Manatee in the Southern Range and Limited Evidence of Hybridization With Amazonian Manatees

Abstract: The Antillean subspecies of the West Indian manatee is classified as endangered by the International Union for the Conservation of Nature (IUCN) Red List. In Brazil, the manatee population is listed as endangered with an estimated population size of 500–1,000. Historic hunting, recent habitat degradation, and fisheries bycatch have decreased the population size. The Amazonian manatee is listed as vulnerable by the IUCN with unknown population sizes within Brazil. The Antillean manatee occurs in sympatry with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 79 publications
(92 reference statements)
1
21
0
Order By: Relevance
“…However, despite this, these two species are found in sympatry in the estuarine region of the Marajó Archipelago, a complex area near the Amazon delta, with rivers, lakes and where fresh and saltwater mix in distinctive patterns according to the rainfall regime [ 3 , 4 , 5 , 6 ]. Because of this, the possible occurrence of hybridization between T. manatus and T. inunguis has been analyzed by means of molecular studies, based on both mitochondrial and molecular DNA markers [ 1 , 7 , 8 ]. Unfortunately, the results of these studies are currently inconclusive [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite this, these two species are found in sympatry in the estuarine region of the Marajó Archipelago, a complex area near the Amazon delta, with rivers, lakes and where fresh and saltwater mix in distinctive patterns according to the rainfall regime [ 3 , 4 , 5 , 6 ]. Because of this, the possible occurrence of hybridization between T. manatus and T. inunguis has been analyzed by means of molecular studies, based on both mitochondrial and molecular DNA markers [ 1 , 7 , 8 ]. Unfortunately, the results of these studies are currently inconclusive [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the results of these studies are currently inconclusive [ 9 ]. Therefore, while mitochondrial DNA (mtDNA) analyses have indicated the occurrence of interspecific hybrids in the estuarine sympatric region [ 1 , 7 ], the sequencing of nuclear (nuDNA) markers did not find evidence of hybridization in individuals sampled in the area, including individuals from the Guianas, proposed as part of the hybrid zone [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the T. m. manatus populations from the Caribbean and up to the Amazon River mouth are phylogenetically closer to the populations of T. m. latirostris from the United States than to the Brazilian T. m. manatus populations south of the Amazon River mouth ( Vianna et al, 2006 ; Barros et al, 2017 ; Lima et al, 2019 , 2021 ). Hybrids between T. manatus and T. inunguis have also been reported on the sympatric area at the Amazon River mouth ( Vianna et al, 2006 ; Lima et al, 2019 ; Luna et al, 2021 ).…”
Section: Introductionmentioning
confidence: 88%
“…Sequences were manually edited and aligned using Geneious Prime (www.geneious.com). In order to detect potential new haplotypes among the new samples included in this study, comparisons with haplotypes defined by García-Rodríguez et al (1998), Cantanhede et al (2005), Vianna et al (2006), Satizábal et al (2012), Lima et al (2019), Vilaça et al (2019), andLuna et al (2021). For T. manatus, these included sequences obtained from Florida, Cuba, Dominican Republic, Puerto Rico, Mexico, Belize, Panama, Colombia, Venezuela, French Guiana, and Brazil.…”
Section: Mtdna Data Analysesmentioning
confidence: 99%